2022
DOI: 10.2147/ccid.s379231
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab for Chronic Prurigo in Different Backgrounds: A Case Series

Abstract: Chronic prurigo (CPG) is a chronic inflammatory disease characterized by intense pruritus, and therapy is often challenging due to its unclear pathogenesis. Here, we report four patients with refractory CPG from different backgrounds who experienced failure of conventional therapy and were controlled with dupilumab, accompanied by a significant decrease in pruritus numerical rating scale, dermatology life quality index, and investigator global assessment, without adverse effects. Furthermore, dupilumab improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Beyond dermatology, dupilumab is also effective and approved for moderate-to-severe asthma, chronic rhinosinusitis with nasal polyposis (CRSwNP) [ 6 ] and eosinophilic esophagitis. In addition, efficacy of dupilumab in prurigo nodularis (PN) and other forms of chronic prurigo was previously shown in several reports [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The phase 3 clinical trials LIBERTY-PN PRIME and PRIME2 showed significantly reduced itch, amelioration of skin lesions, sleep, pain and quality of life compared to placebo treatment in a total of 153 treated patients (NCT04202679, NCT04183335).…”
Section: Introductionmentioning
confidence: 99%
“…Beyond dermatology, dupilumab is also effective and approved for moderate-to-severe asthma, chronic rhinosinusitis with nasal polyposis (CRSwNP) [ 6 ] and eosinophilic esophagitis. In addition, efficacy of dupilumab in prurigo nodularis (PN) and other forms of chronic prurigo was previously shown in several reports [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The phase 3 clinical trials LIBERTY-PN PRIME and PRIME2 showed significantly reduced itch, amelioration of skin lesions, sleep, pain and quality of life compared to placebo treatment in a total of 153 treated patients (NCT04202679, NCT04183335).…”
Section: Introductionmentioning
confidence: 99%